Methanethiol Consumption and Hydrogen Sulfide Production by the Thermoacidophilic Methanotroph Methylacidiphilum fumariolicum SolV - Schmitz, Rob A.; Mohammadi, Sepehr S.; van Erven, Timo; Berben, Tom; Jetten, Mike S. M.; Pol, Arjan; Op den Camp, Huub J. M. (Frontiers in Microbiology, 2022)
Methanotrophs aerobically oxidize methane to carbon dioxide to make a living and are known to degrade various other short chain carbon compounds as well. Volatile organic sulfur compounds such as methanethiol (CH3SH) are important intermediates in the sulfur cycle. Although volatile organic sulfur compounds co-occur with methane in various environments, little is known about how these compounds affect methanotrophy. The enzyme methanethiol oxidase catalyzing the oxidation of methanethiol has been known for decades, but only recently the mtoX gene encoding this enzyme was identified in a methylotrophic bacterium. The presence of a homologous gene in verrucomicrobial methanotrophs prompted us to examine how methanotrophs cope with methanethiol. Here, we show that the verrucomicrobial methanotroph Methylacidiphilum fumariolicum SolV consumes methanethiol and produces H2S, which is concurrently oxidized. Consumption of methanethiol is required since methanethiol inhibits methane oxidation. Cells incubated with ~ 15 µM methanethiol from the start clearly showed inhibition of growth. After depletion of methanethiol, growth resumed within one day. Genes encoding a putative methanethiol oxidase were found in a variety of methanotrophs. Therefore, we hypothesize that methanethiol degradation is a widespread detoxification mechanism in methanotrophs in a range of environments.